Size Gynomimicry in the Sanmartinero Creole Bovine of the Colombian Orinoquia (2024)
Variations in the size of animals of the same species but of different sex are called sexual size dimorphism. The aim of this study was to compare the biometrics between males and females of the Sanmartinero creole bovine, of Colombia, to establish if sexual dimorphism appears in the breed. A total of 94 animals (16 uncastrated males and 78 females, average age of 4.3 ± 1.4 and 4.2 ± 2.3 years, respectively) from three different farms were measured. A total of 21 linear variables were obtained using standard morphometric methods and live weight. A one-way NPMANOVA was used to evaluate between sexes, ages, and farms, a Principal Component Analysis was used to detect the most discriminating variables, and a multivariate regression used age as an independent value. Statistically significant differences were reflected between sexes (p = 0.033) and not by age and farms. The variables that differentiated the most between males and females were those related to size (thoracic circumference, body length, dorso-sternal diameter, height at the withers, height at the rump, and horn length), variables that were biased toward males, although only the height at the withers and the rump were the ones that presented statistically significant differences.